Pelatihan Pengolahan Kemiri dan Kacang Sacha Inchi Menjadi Produk Unggulan Lokal untuk Meningkatkan Perekonomian Masyarakat Desa Tanak Beak - Irman Muliadi; Satutik Rahayu; Novianti Ramdani; Lira Nurman Abista; Angga Mulyadin; Ni Putu Deanita Dewanti; Denda Naya Sagiantari; Ardian Kurnia Hanispi; Harfina Suharis Fiana; Reva Nur Ramadhani; Zulfia Salsabila (Indonesian Journal of Education and Community Services, 2026)
Tanak Beak Village possesses abundant potential in candlenut and Sacha Inchi bean commodities; however, their utilization remains suboptimal due to the community's dependence on selling raw materials at low market prices. This study aims to transform these local commodities into flagship products through processing training programs and digital marketing strategies to improve the community's economic welfare. The community service method was implemented through the University of Mataram's KKN PMD program over 45 days, encompassing preparation (surveys and interviews), implementation (product diversification and seminars), and evaluation stages. Research instruments included observation sheets, interviews, and pre- and post-test questionnaires. The results indicate that food technology intervention successfully processed candlenuts into "Packaged Roasted Candlenuts" and Sacha Inchi Bean into snack products. Evaluation via n-gain scores showed a significant increase in participants' knowledge, rising from an average of 50.30 to 94.03, with an effectiveness value of 0.88 (high category). From an economic perspective, a 10-day market trial demonstrated high interest, with sales exceeding 50 product packages. Furthermore, graphic design training using Canva and social media marketing proved effective in expanding market reach. This program has successfully provided concrete solutions for the community in increasing the added value of local products and fostering digital-based economic independence.